2018
DOI: 10.1021/acs.nanolett.8b01845
|View full text |Cite
|
Sign up to set email alerts
|

Ultrascaled Germanium Nanowires for Highly Sensitive Photodetection at the Quantum Ballistic Limit

Abstract: We report an experimental study on quasi-one-dimensional Al-Ge-Al nanowire (NW) heterostructures featuring unmatched photoconductive gains exceeding 10 and responsivities as high as 10 A/μW in the visible wavelength regime. Our observations are attributed to the presence of GeO related hole-trapping states at the NW surface and can be described by a photogating effect in accordance with previous studies on low-dimensional nanostructures. Utilizing an ultrascaled photodetector device operating in the quantum ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“… 23 The surface of Ge NWs with typical interface trap densities of 10 13 –10 14 /(eV cm 2 ), 24 up to three orders of magnitude higher compared to planar Ge structures, corresponding to roughly 0.2–2% of the surface atoms, 36 provide a large reservoir of such trap states, which act as a highly efficient local gate. 18 Considering the Ge NW device shown in Figure 1 a, a maximum of 20 000 traps are involved in determining the device behavior. With time constants in the range from microseconds to several minutes for interface and oxide states respectively, 37 one cannot avoid hysteresis effects for dynamic measurements of Ge NW FETs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 The surface of Ge NWs with typical interface trap densities of 10 13 –10 14 /(eV cm 2 ), 24 up to three orders of magnitude higher compared to planar Ge structures, corresponding to roughly 0.2–2% of the surface atoms, 36 provide a large reservoir of such trap states, which act as a highly efficient local gate. 18 Considering the Ge NW device shown in Figure 1 a, a maximum of 20 000 traps are involved in determining the device behavior. With time constants in the range from microseconds to several minutes for interface and oxide states respectively, 37 one cannot avoid hysteresis effects for dynamic measurements of Ge NW FETs.…”
Section: Resultsmentioning
confidence: 99%
“…As already demonstrated, at T = 80 K, a redistribution of traps by the means of electrostatic gating is kinetically blocked. 18 , 23 Consequently, it should be possible to freeze-in the transport regime based on the polarity of the device set at room temperature. Thus, by cooling down the Ge NW device, which was previously depleted for 60 min at V G = −15 V, one can conserve the polarity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 ] At the same time, emerging distributed computing paradigms such as the Internet of Things [ 3 ] are placing extraordinarily stringent constraints on hardware performance, forcing a shift of research efforts towards the integration of new materials, processes, and device architectures. [ 4–6 ] In this context, low‐dimensional Ge structures such as nanomembranes [ 7,8 ] and vapor‐liquid‐solid [ 9 ] (VLS) grown nanowires [ 10,11 ] (NWs), exhibiting unique electrical [ 4,10,12 ] and optical [ 13–15 ] properties departing from their bulk counterparts, are considered key building blocks in a “More than Moore” approach extending device performances beyond the limits imposed by miniaturization. [ 16,17 ] In this respect, a highly interesting transport mechanism is the transferred electron effect, enabling negative differential resistance (NDR) following the Ridley–Watkins–Hilsum theory.…”
Section: Introductionmentioning
confidence: 99%
“…Combining kinetic studies of the reaction interface with three-dimensional chemical modeling, a surface diffusion mechanism in the Al/ Ge binary nanowire system is proposed where Ge atoms diffuse through a surface diffusion channel on the created Al NW into the Al contact pad, whereas Al atoms are supplied to the reaction interface by Al self-diffusion and exchange with Ge atoms at the interface. The electrical and optical transport properties of ultrascaled Al/Ge/Al heterostructures were elucidated in the work of Sistani et al 23 and Staudinger et al, 24 where they showed quantum ballistic transport as well as quantum ballistic photodetection at room temperature. The Al/Ge system in NWs appears very promising since, in contrast to other metal−semiconductor combinations, no intermetallic phase is formed, and a pure monocrystalline Al NW is created with a very sharp interface with the remaining Ge NW.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we demonstrate a proof of principle fabrication of a sub-10 nm semiconductor quantum disk using the combination of ex-situ and in-situ heating methods, which could be key for the future production of ultrascaled devices. Most notably, this exemplary selective replacement of Ge by Al might represent a general approach for the elaboration of ultrascaled radial , and axial , metal–semiconductor heterostructures in various Ge–semiconductor heterostructures, and in-situ TEM optimization of this reaction may be of great value before a real upscaling.…”
Section: Introductionmentioning
confidence: 99%